Editor's Choice – Management of the Diseases of Mesenteric Arteries and Veins: Clinical Practice Guidelines of the European Society of Vascular Surgery (ESVS). (April 2017) - Björck, M.; Koelemay, M.; Acosta, S.; Bastos Goncalves, F.; Kölbel, T.; Kolkman, J.J.; Lees, T.; Lefevre, J.H.; Menyhei, G.; Oderich, G.; ESVS Guidelines Committee,; Kolh, P.; et al.
Abstract : Dedication: These guidelines are dedicated to Paola De Rango, University of Perugia, Italy. She participated very actively in the process of developing these guidelines, in particular the important chapters on chronic arterial and venous mesenteric ischaemia. Six days after the second meeting of the task force she died unexpectedly, to our great despair and loss. We honour her dedication and scientific integrity by completing these guidelines. Among many other commitments she was a very productive reviewer and an associate editor of this journal. You can read more about Paola's important contributions to science and to the vascular community in the April 2016 issue of the European Journal of Vascular and Endovascular Surgery . 1 Dr Paola De Rango, July 28, 1966 – February 21, 2016